Divalent Transition Metals Substituted LaFeO3 Perovskite Catalyst for Nitrous Oxide Decomposition - Medkhali, Asma H.A.; Narasimharao, Katabathini; Basahel, Sulaiman N.; Mokhtar, Mohamed (Journal of Membrane and Separation Technology, 2014)
Divalent transition metals substituted LaFeO3 type perovskite catalysts (LaFe0.95M0.05O3 with M= Cu2+ and Ni2+) were synthesized by hydrothermal method and characterized by using X-ray diffraction (XRD), temperature programmed reduction with H2 (H2-TPR) and N2-physisorption techniques. The catalytic activity of the catalysts was tested for N2O decomposition reaction. Enhancement in the catalytic activity was observed after substitution of Cu and Ni metal ions into LaFeO3 framework. LaFe0.95Ni0.05O3 showed higher catalytic activity than LaFeO3 and LaFe0.95Cu0.05O3 catalysts. The plausible reason for the increased activity is that LaFe0.95Ni0.05O3 sample possessed high oxygen mobility than the other two samples.